Islam and religious change in Pakistan: Sufis and Ulema in 20th century South Asia - Sumbal, Saadia (Routledge South Asian religion series, 2022)
Introduction -- 1. Migrant Sufis and Rooting of Islam (ca. 1600-1900) -- 2. Islamic Reformism and Shrine-based Religiosity: A Dialectical Identity -- 3. Reformist Islam: Emergence of Communal Identities and Politics of Nationalism -- 4. Sectarianism and The Politics of Religious Exclusion -- 5. Assertion of Deobandi Identity and Widening of Sectarian Cleavage -- Conclusion -- Appendixes -- Bibliography -- Glossary -- Index.